Junção e(m) aquisição: aspectos morfossintáticos e cognitivos - Longhin-Thomazi, Sanderleia Roberta [UNESP] (My University, 2011)
In this work, I start out from a junction to investigate possible correlations between the underlying trends in the use of the junction mechanisms in subject texts during the writing acquisition stage, as well as trends in the development of junctures in language history. In a certain way, the purpose is to bring new light to the parallel between ontogeny and phylogeny, as proposed by Kortmann (1997), who supports, for the acquisition of junction schemes and for the change of junctures over time, directions which signal a growing complexity, verifiable both through a morphosyntactic and cognitive-semantic point of view.

Neste trabalho, investigo possíveis correlações entre tendências subjacentes aos usos dos mecanismos de junção em textos de sujeitos em fase de aquisição de escrita e tendências sobre desenvolvimento de juntores na história da língua. Trata-se, de certa maneira, de trazer novas luzes acerca do paralelo entre ontogenia e filogenia, nos moldes de Kortmann (1997), que sustenta, para a aquisição de esquemas de junção e para a mudança dos juntores ao longo do tempo, direções que sinalizam uma complexidade crescente, verificável tanto de um ponto de vista morfossintático, como de um ponto de vista semântico-cognitivo.
Keywords: aquisição; junção; cognição; história; Acquisition; junction; cognition; history